The Effectiveness of Sonic-Activated Irrigation in Reducing Intratubular Enterococcus faecalis - Ghoddusi, Jamileh; Moushekhian, Siavash; Arian, Ehsan; Ghiasi, Javad; Forghani, Maryam (Iranian Endodontic Journal, 2019)
Introduction: The purpose of this in vitro study was to compare the effectiveness of sonic activation and syringe irrigation of 5.25% sodium hypochlorite in removing the Enterococcus faecalis (E. faecalis) biofilm. Methods and Materials: Root canals of 54 extracted human single-rooted central incisors were prepared with ProTaper S1-S2-F1-F2 and Gates Gliden burs size 1, and 2 at the working length. After sterilization, the root canals were contaminated with E. faecalis suspension and randomly assigned to three groups: G1, conventional syringe irrigation; G2, sonic agitation of NaOCl with Endo Activator system; and G3, no subjected to the mentioned irrigation techniques (negative control). Canals were sampled after the disinfection procedure. The colony forming units (CFU) count was evaluated. Samples were also visualized under fluorescent microscope to count viable bacteria. Data were statistically analyzed using the Kruskal-Wallis and one-way ANOVA followed by Tukey’s test (P<0.05). Results: There was a significant reduction in the CFU count after both irrigation techniques. There was no significant difference between two techniques (P=0.874). Using bacterial viability kit, Endo Activator displayed the least viable bacteria than the other groups (P<0.001) and control group showed the greatest one (P<0.001). Conclusion: In this in vitro study, the Endo Activator system was more successful in reducing intratubular viable bacteria compared with NaOCl syringe irrigation alone. Keywords: Enterococcus faecalis; Irrigation; Root Canal Disinfection; Sodium Hypochlorite; Sonic Irrigation